CNTNAP1-encephalopathy: Six novel patients surviving the neonatal period. (March 2022) - Garel, Pauline; Lesca, Gaetan; Ville, Dorothée; Poulat, Anne-Lise; Chatron, Nicolas; Sanlaville, Damien; Des Portes, Vincent; Arzimanoglou, Alexis; Lion-François, Laurence
Abstract: CNTNAP1 encodes CASPR1, involved in the paranodal junction. Thirty-three patients, with CNTNAP1 biallelic mutations have been described previously. Most of them had a very severe neurological impairment and passed away in the first months of life. We identified four patients, from two unrelated families, who survived over the neonatal period. Exome sequencing showed compound heterozygous or homozygous variants. Severe hypotonia was a constant feature. When compared to previous reports, the most important clinical differences observed in our patients were the absence of antenatal problems and, in two of them, the lack of respiratory distress. Less commonly reported characteristics such as epileptic seizures, dystonia, and impaired communication skills were also observed. MRIs revealed hypomyelination or abnormal white matter signal, cerebral or cerebellar atrophy. The present observations support a wider than initially reported clinical spectrum, including survival after the neonatal period and additional neurological features. They contribute to better delineate the phenotype–genotype correlations for CNTNAP1. In addition, we report one more family with two sibs who carry a missense variant of uncertain significance which we propose could be associated with a milder phenotype. Highlights: CNTNAP1 mutations appear as a novel aetiology for severe hypotonia in newborns and infants. This study confirms that survival after infancy can occur in patients with CNTNAP1 pathogenic variants. Clinical spectrum is extended with new cases of dystonia, better motor and communication skills than previously described. Three novel missense variants are described.